Factors related with the appropriateness of pharmacological treatment in polypathological patients - M.D. Vega Coca; P.C. Rivas Covas; E.R. Alfaro Lara; M. Rincón Gómez; M. Galván Banqueri; M.D. Nieto Martín (Farmacia Hospitalaria)
Objective: To evaluate the association between the number of pharmacological inappropriateness and possible factors related with it.